2013
DOI: 10.1038/modpathol.2013.62
|View full text |Cite
|
Sign up to set email alerts
|

The liver in itai-itai disease (chronic cadmium poisoning): pathological features and metallothionein expression

Abstract: Cadmium (Cd) is a highly hepatotoxic heavy metal, which is widely dispersed in the environment. Acute Cd hepatotoxicity has been well studied in experimental animals; however, effects of prolonged exposure to Cd doses on the liver remain unclear. In the present study, to evaluate chronic Cd hepatotoxicity, we examined specimens from cases of itai-itai disease, the most severe form of chronic Cd poisoning. We compared 89 cases of itai-itai disease with 27 control cases to assess Cd concentration in organs. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(60 citation statements)
references
References 30 publications
(31 reference statements)
1
58
0
1
Order By: Relevance
“…Our analysis also showed that Cd concentration tended to decrease as the Cd-induced kidney injury advanced in severity. We previously reported the same tendency also in the liver of IID patients (Baba et al, 2013). Our findings strongly support the conventional idea.…”
Section: Discussionsupporting
confidence: 81%
“…Our analysis also showed that Cd concentration tended to decrease as the Cd-induced kidney injury advanced in severity. We previously reported the same tendency also in the liver of IID patients (Baba et al, 2013). Our findings strongly support the conventional idea.…”
Section: Discussionsupporting
confidence: 81%
“…We hypothesize that cadmium is released from tissues. Liver is well-known to accumulate cadmium; lower levels of cadmium in muscle, making up a larger fraction of total body mass, may also contribute(14, 30, 41, 42). …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Cd can also produce toxicity to other systems of human body, and even induce cell distortion and cancerization (Wu, 2015). One of the most famous accidents was the “Itai-Itai Disease” that occurred in Toyama Prefecture of Japan in 1960s (Baba et al, 2013). Several events of human Cd poisoning resulting from soil Cd pollution have subsequently been reported around the world (Sterckeman et al, 2000; Du et al, 2013).…”
Section: Introductionmentioning
confidence: 99%